Comparison of Corneal Endothelial Cells Loss After Phacoemulsification between Dispersive- Cohesive Viscoelastic (Soft Shell) and Adaptive Viscoelastic in Hard Density Senile Cataract - Elvita Marer; Budiman Budiman; Irawati Irfani (Majalah Oftalmologi Indonesia, 2016)
Background: Phacoemulsification cataract surgery can cause endothelial damage. Endothelial damageduring phacoemulsification is caused by ultrasound energy (power), fluid turbulence, trauma by lensfragment, and the formation of air bubbles. To protect the corneal endothelium during phacoemulsification,we can use two types of dispersive and cohesive viscoelastic simultaneously (soft shell); dispersiveviscoelastic not entirely in aspiration, but still coats the endothelium during phacoemulsification. Theaim of this study is to compare the corneal endothelial cell loss one month after phacoemulsificationcataract surgery between dispersive-cohesive viscoelastic (soft shell) and adaptive viscoelastic in hardlens nucleus.Methods: This study was randomised clinical trials. Subjects were mature senile cataract patients,aged â‰¥50 years old, who came to Cataract and Refractive Surgery Unit at Cicendo Eye Hospital.Selection of the sample was consecutive admission, divided into two groups: dispersive-cohesiveviscoelastic (soft shell) and adaptive viscoelastic up to 13 samples per group. Examinations of cornealendothelial cells pre-surgical and one month post surgical were performed by a nurse in the diagnosticunit at Cicendo Eye Hospital, Bandung, by using specular microscope.Results: Corneal endothelial cell loss one month post surgery in the soft shell group was 1467.55 cells/mm2(59.09%) and adaptive viscoelastic group was 1682.3 cells/mm2 (60.32%). There was no statisticallysignificant difference between the two groups (p=0.184).Conclusion: Loss of post-operative corneal endothelial cells in cataract degree 5 and 6 was not statisticallysignificant between soft shell an adaptive viscoelastic group.Â Keywords: phacoemulsification, dispersive-cohesive (soft shell), corneal endothelial cells, specular microscope